Pengaruh Kesadaran Wajib Pajak dan Moral Wajib Pajak Terhadap Kepatuhan Wajib Pajak UMKM di Kota Bekasi - Nursifah Marwah; Daryanto Hesti Wibowo (Jurnal Ilmu Administrasi Publik, 2023)
The contribution of MSMEs to the National Gross Domestic Product (GDP) according to current prices in 2018 is around 60% or 60 million,  but  only  1.5  million  pay  taxes  or  2.2%  of  income  tax receipts. Then, as of April 1, 2019 the Directorate General of Taxes recorded the realization of annual notification letter reporting (SPT) of  11.309  million  people,  or  the  equivalent  of  61.7%  of  18.334 million taxpayers. This shows that there is still low awareness and compliance with taxation by taxpayers. This research wants to make an  academic  contribution  to  the  picture  of  optimizing  the  tax potential  of  Micro,  Small,  and  Medium  Enterprises  (MSMEs) through the Awareness and Moralty approach. The type of research used id explanatory with a quantitative approach. The research was conducted on a sample of Small and Medium Enterprises (SMEs) in Bekasi  City  (West  Bekasi).  The  hypotheses  tested  are  1)    The significant effect of Taxpayer Awareness on Tax payer Compliance of   Micro,   Small,   and   Medium   Enterprises   (MSMEs);   2)    The significant influence of Taxpayer Morale on Taxpayer Compliance; 3)      Simultaneously    and   significantly   the   effect   of   Taxpayer Compliance of Micro, Small, and Medium Enterprises (MSMEs).